Pharmacokinetics and Dialytic Clearance of Ceftazidime-Avibactam in a Critically Ill Patient on Continuous Venovenous Hemofiltration - Wenzler, Eric (Antimicrob Agents Chemother, 2017)
Ceftazidime-avibactam administered at 1.25 g every 8 h was used to treat multidrug-resistant Pseudomonas aeruginosa bacteremia in a critically ill patient on continuous venovenous hemofiltration (CVVH). Prefiltration plasma drug concentrations of ceftazidime and avibactam were measured at 0, 1, 2, 4, 6, and 8 h along with postfiltration and ultrafiltrate concentrations at h 2 and h 6. Plasma pharmacokinetic parameters of ceftazidime and avibactam, respectively, were as follows: maximum plasma concentration (C(max)), 61.10 and 14.54 mg/liter; minimum plasma concentration (C(min)), 31.96 and 8.45 mg/liter; half-life (t(1/2)), 6.07 and 6.78 h; apparent volume of distribution at the steady state (V(ss)), 27.23 and 30.81 liters; total clearance at the steady state (CL(ss)), 2.87 and 2.95 liters/h; area under the concentration-time curve from 0 to 8 h (AUC(0–8)), 347.87 and 85.69 mg · h/liter. Concentrations of ceftazidime in plasma exceeded the ceftazidime-avibactam MIC (6 mg/liter) throughout the 8-h dosing interval. Mean CVVH extraction ratios for ceftazidime and avibactam were 14.44% and 11.53%, respectively, and mean sieving coefficients were 0.96 and 0.93, respectively. The calculated mean clearance of ceftazidime by CVVH was 1.64 liters/h and for avibactam was 1.59 liters/h, representing 57.1% of the total clearance of ceftazidime and 54.3% of the total clearance of avibactam. Further data that include multiple patients and dialysis modes are needed to verify the optimal ceftazidime-avibactam dosing strategy during critical illness and CVVH.